“Movable Membrane” Innovative Educational Complex for Intelligent Agriculture - Badalyan, Astghik; Karsyan, Patrisia; Petrosyan, Anahit (Scientific Papers of National University of Architecture and Construction of Armenia, 2024)
The potential for advancing smart agriculture in Armenia’s rural communities is highlighted through educational initiatives, alongside the advantageous conditions for deploying innovative mobile modular prefabricated constructions. The objective and challenges draw from international insights, aiming to examine the agricultural makeup of administrative territorial units through a typological analysis of Armenia’s expanded rural communities. This approach seeks to thoroughly explore the structural characteristics inherent in their constituent elements, employing a method that integrates complex design principles based on the mobile modular concept. We examined the key design principles of mobile complex constructions, integrating professional features and addressing challenges in smart agriculture. Our proposal emphasizes the advantages of employing portable units that can move efficiently from one community to another, facilitating convenient education initiatives for local residents. Favorable conditions are being established for the implementation of defense military training programs in border communities, within designated zones allocated for this purpose. We introduce the conceptual design of an innovative training complex that is portable, rapidly deployable, adaptable to varying terrains, self-sustaining in terms of electricity, and resource-efficient. This design not only serves the purpose of defense training but also contributes to the advancement of communities by promoting the adoption of smart agriculture practices.